2004
DOI: 10.1161/01.cir.0000128696.12245.57
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor–Mediated Vasodilation in Human Coronary Microarteries

Abstract: Background-Angiotensin (Ang) II type 2 (AT 2 ) receptor stimulation results in coronary vasodilation in the rat heart. In contrast, AT 2 receptor-mediated vasodilation could not be observed in large human coronary arteries. We studied Ang II-induced vasodilation of human coronary microarteries (HCMAs). Methods and Results-HCMAs (diameter, 160 to 500 m) were obtained from 49 heart valve donors (age, 3 to 65 years).Ang II constricted HCMAs, mounted in Mulvany myographs, in a concentration-dependent manner (pEC 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
127
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 47 publications
14
127
0
1
Order By: Relevance
“…It was reported recently that AT 2 R-mediated vasodilation occurs in the coronary microcirculation of nondiseased hearts in a cohort of subjects with a wide age range. 16 As well, in healthy young subjects treated for 1 week with an AT 1 R antagonist, intrabrachial arterial infusion of the AT 2 R antagonist PD123319 resulted in increased BP, with no changes in forearm vascular responses. 27 Ang II elicited dose-dependent AT 2 R-mediated vasodilation only in resistance arteries from hypertensive diabetic patients treated for 1 year with valsartan.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was reported recently that AT 2 R-mediated vasodilation occurs in the coronary microcirculation of nondiseased hearts in a cohort of subjects with a wide age range. 16 As well, in healthy young subjects treated for 1 week with an AT 1 R antagonist, intrabrachial arterial infusion of the AT 2 R antagonist PD123319 resulted in increased BP, with no changes in forearm vascular responses. 27 Ang II elicited dose-dependent AT 2 R-mediated vasodilation only in resistance arteries from hypertensive diabetic patients treated for 1 year with valsartan.…”
Section: Discussionmentioning
confidence: 88%
“…15 AT 2 Rs have been demonstrated in the human coronary microcirculation, where they may contribute to vasodilation. 16 Studies in cellular and animal models suggest that AT 2 R counteracts many AT 1 R actions by inducing vasodilation, antiproliferation, and apoptosis. 2 We showed recently in animal models of hypertension that AT 2 R is upregulated and mediates vasodilation only when AT 1 Rs are blocked, 6,7 suggesting that AT 2 R participates in the mechanisms whereby Ang II receptor antagonism lowers blood pressure (BP).…”
mentioning
confidence: 99%
“…This acute angiotensin AT 2 receptor-mediated vasodilator response may be endothelium-dependent or independent and appears to involve a range of signaling pathways, including nitric oxide and bradykinin production, activation of cytochrome P-450 epoxygenase pathways and modulation of K + channel activity (Widdop et al, 2003). Moreover, in the human heart, it has been recently shown that angiotensin AT 2 receptor stimulation in coronary microarteries induces endothelium-dependent vasodilation which is mediated by bradykinin B 2 receptors and nitric oxide (Batenburg et al, 2004a). Nitric oxide released either from cardiac endothelial cells or generated within cardiac myocytes can directly influence cardiac contractile function (Shah et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…They are expressed in human skin 33,34 and in the coronary circulation. 35 In the adult human renal cortex, AT 2 receptor mRNA is mainly expressed in interlobular arteries. 36 Effects of Ang II on blood pressure and sodium-volume homeostasis Ang II increases arterial pressure via two principal effects.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%
“…In general, it is assumed that AT 2 receptors oppose the responses mediated by AT 1 receptors. 35,75,76 Although the AT 1 receptor is involved in pressor, vasoconstrictor and antinatriuretic effects, the AT 2 receptor appears to mediate depressor effects, vasodilation and natriuresis. 77,78 AT 2 receptor stimulation could increase the production of NO and cGMP either by increasing bradykinin production and bradykinin B2 receptor stimulation or by direct activation of NO production.…”
Section: Angiotensin II At 1 and At 2 Receptorsmentioning
confidence: 99%